A educação formal de mulheres reclusas no sistema prisional do município de Uberlândia: realidade e utopia - Teófilo , Tânia de Fátima (2023)
ABSTRACT This study is the result of research at the Master's level in the research line State and Politics and Management in Education, from the Graduate Program in Education at Uberlandia Fed-eral University. The general objective of the research is to analyze the social and institutional ideological factors that favor or limit the adherence of female inmates to formal education within the prison system, and has as it background “Professor Jacy de Assis” Correctional Facility and the “Professor Paulo Freire” State School, located in the city of Uberlândia, state of Minas Gerais, Brazil. To achieve the proposed objective, documental, bibliographical and field research techniques were used, through the application of questionnaires to 19 female inmates, 02 managers and 06 education professionals, linked to the two investigated institu-tions. The methodology is based on the practice of qualitative research and the content analy-sis of the interviews carried out through the application of the dialectic-hermeneutic method (MINAYO, 2004). As part of the theoretical foundation, the first section addresses the theme of “women in society: violence, social prejudice and deprivation of liberty - critical aspects”. The second, called “Education in Prison Units”, addresses the regulations, legalization and formal structure of educational policies for the prison system in Brazil and in the state of Mi-nas Gerais, as well as the history of “Professor Jacy de Assis” Correctional Facility and “Pro-fessor Paulo Freire” State School. The third section refers to the study of “Freedom, social, institutional and ideological factors that favor and limit the participation of demale inmates in school education in the prison system in the “Professor Jacy de Assis Prison” and presents the results and final analysis of this present study. research. Among the results found, under the bias of gender and prison conjuncture policies, factors were identified that may interfere in the decision-making process by female inmates regarding their willingness to enroll formal educa-tion in the researched prison unit. The written testimonies of the women participating in the research pointed to the recognition of the value of the education received in prison; the im-portance of the welcoming environment received by the pedagogical team, consisting of spac-es for listening, for valuing human beings, and for the possibility of envisioning a professional future capable of improving their economic and social living conditions. Faced with the study of the journey of the condition of women in society, at different times, with emphasis on those who are in the condition of deprivation of liberty in Brazil and in the State of Minas Gerais and the experiences and expectations of school administrators, teachers and female inmates in the prison system, a set of factors was also identified that hinder and/or contribute to the formal education of women inmates in “Professor Jacy de Assis” Correctional Facility, from 2006 through 2019.